Designing a synthetic microbial community devoted to biological control: The case study of Fusarium wilt of banana - Prigigallo, Maria Isabella; Gómez-Lama Cabanás, Carmen; Mercado-Blanco, Jesús; Bubici, Giovanni (Frontiers in Microbiology, 2022)
Fusarium oxysporum f. sp. cubense (Foc) tropical race 4 (TR4) is threatening banana production because of its increasing spread. Biological control approaches have been widely studied and constitute interesting complementary measures to integrated disease management strategies. They have been based mainly on the use of single biological control agents (BCAs). In this study, we moved a step forward by designing a synthetic microbial community (SynCom) for the control of Fusarium wilt of banana (FWB). Ninety-six isolates of Pseudomonas spp., Bacillus spp., Streptomyces spp., and Trichoderma spp. were obtained from the banana rhizosphere and selected in vitro for the antagonism against Foc TR4. In pot experiments, a large community such as SynCom 1.0 (44 isolates with moderate to high antagonistic activity) or a small one such as SynCom 1.1 (seven highly effective isolates) provided similar disease control (35% symptom severity reduction). An in vitro study of the interactions among SynCom 1.1 isolates and between them and Foc revealed that beneficial microorganisms not only antagonized the pathogen but also some of the SynCom constituents. Furthermore, Foc defended itself by antagonizing the beneficial microbes. We also demonstrated that fusaric acid, known as one of the secondary metabolites of Fusarium species, might be involved in such an interaction. With this knowledge, SynCom 1.2 was then designed with three isolates: Pseudomonas chlororaphis subsp. piscium PS5, Bacillus velezensis BN8.2, and Trichoderma virens T2C1.4. A non-simultaneous soil application of these isolates (to diminish cross-inhibition) delayed FWB progress over time, with significant reductions in incidence and severity. SynCom 1.2 also performed better than two commercial BCAs, BioPak® and T-Gro. Eventually, SynCom 1.2 isolates were characterized for several biocontrol traits and their genome was sequenced. Our data showed that assembling a SynCom for biocontrol is not an easy task. The mere mixtures of antagonists (e.g., SynCom 1.0 and 1.1) might provide effective biocontrol, but an accurate investigation of the interactions among beneficial microorganisms is needed to improve the results (e.g., SynCom 1.2). SynCom 1.2 is a valuable tool to be further developed for the biological control of FWB.